Current Applications of Artificial Intelligence in Cleft Care: A Scoping Review - Dhillon, Harnoor; Chaudhari, Prabhat Kumar; Dhingra, Kunaal; Kuo, Rong-Fu; Sokhi, Ramandeep Kaur; Alam, Mohammad Khursheed; Ahmad, Shandar (Frontiers in Medicine, 2021)
OBJECTIVE: This scoping review aims to identify the various areas and current status of the application of artificial intelligence (AI) for aiding individuals with cleft lip and/or palate. INTRODUCTION: Cleft lip and palate contributes significantly towards the global burden on the healthcare system. Artificial intelligence is a technology that can help individuals with cleft lip and/or palate, especially those in areas with limited access to receive adequate care. INCLUSION CRITERIA: Studies that used artificial intelligence to aid the diagnosis, treatment, or its planning in individuals with cleft lip and/or palate were included. METHODOLOGY: A search of the Pubmed, Embase, and IEEE Xplore databases was conducted using search terms artificial intelligence and cleft lip and or/ palate. Grey literature was searched using Google Scholar. The study was conducted according to the PRISMA- ScR guidelines. RESULTS: The initial search identified 458 results, which were screened based on title and abstracts. After the screening, removal of duplicates, and a full-text reading of selected articles, 26 publications were included. They explored the use of AI in cleft lip and palate to aid in decisions regarding diagnosis, treatment, especially speech therapy, and prediction. CONCLUSION: There is active interest and immense potential for the use of artificial intelligence in cleft lip and palate. Most studies currently focus on speech in cleft lip and/or palate. Multi-center studies that include different populations, with collaboration amongst academicians and researchers, can further develop the technology.